MicroRNA profiling of the human stress response - Anett Mueller (European Journal of Psychotraumatology, 2012)
Rationale/statement of the problem : The impact of psychosocial stress on a variety of negative health outcomes is well documented, with much of the current research efforts directed at possible mechanisms. For example, psychosocial stress in humans has recently been associated with DNA damage that plays a role in the etiology of negative health outcomes, and also with changes in DNA transcription to messenger Ribonucleic Acid (mRNA). We have become interested in one putative regulatory element in mRNA translation to proteins: microRNA (miRNA). In this study, we aimed to investigate the relationship between psychosocial stress and changes in gene expression changes on the miRNA level, and to further investigate whether stressful life events and personality traits moderate these relationships. Methods : Using a pre-post design, 36 adults were exposed to standardized psychosocial stress in the laboratory (Trier Social Stress Test [TSST]) and completed measures on perceived and chronic stress. In addition, cortisol levels were determined from saliva samples obtained prior to stressor and at eight time points during recovery. Before and after the TSST, subjects underwent a total of three blood draws from which peripheral blood mononuclear cells (PBMCs) were extracted in order to determine miRNA gene expression levels, using the Affymetrix Genechip 2.0 microRNA array. RNA was extracted from each sample and gene expression was measured by hybridization to the miRNA microarray. In an effort to identify a miRNA expression profile for the acute stress response, we compared miRNA expression changes at baseline (before onset of the stressor) with miRNA expression at the two time points following the stressor. Results : The acute psychosocial stressor produced a higher cortisol response in a subset of the study participants (high responders). We expect these individuals to exhibit significant changes in miRNA expression from baseline to post-stress. We further hypothesize that these changes will be most significant for miRNAs that regulate expression of genes associated with the cortisol stress response. Conclusion : Our study aims to identify a miRNA signature of social stress and to correlate differences in miRNA expression with psychological variables such as early life stress and resilience, which may function to mitigate the stress response.